Editorial: How the Centre of Malaysian Politics Shifted to the Islamist Register 1969-2009 - Editor Al-Jami'ah: Journal of Islamic Studies (Al-Jami'ah Research Centre, 2009)
One of the most obvious observations that can be made about the form and content of Malaysian politics, political discourse and political culture today is how the country has shifted to a visibly more Islamist register, with the symbols and vocabulary of political Islam gaining prominence and visibility over the past four decades. This is particularly true in the case of Malaysia’s civil society space, which was once dominated by secular Non-Governmental Organisations (NGOs), mass movements and lobby groups. Today, however, we are looking at the relatively new phenomenon of a Malaysian civil society space which is increasingly being dominated by Islamist civil society movements that operate within the constitutional framework of the country but which are pushing for a clearly religious-communitarian agenda, namely the Islamisation of Malaysian society and politics. How did this come about?